Friendliness of DCCP towards TCP over large delay link networks - Awang Nor, Shahrudin; Hassan, Suhaidi; Ghazali, Osman; Che Mohamed Arif, Ahmad Suki (2010)
The need for TCP friendly transport protocol is vital for the future Internet. With this motivation, IETF has defined a new transport protocol, DCCP, to be a friendly transport protocol when coexist with other congestion-controlled transport protocol such as TCP. DCCP is an unreliable transport protocol which is designed to be able to carry unreliable time sensitive data traffic such as audio or video streaming with built-in congestion control. Therefore, DCCP can carry streaming data same as UDP but this new transport protocol can adjust the transmission data rate according to the condition of the network. I n case of congestion, the sending data rate will be slowed down for the network to function well so that other transport protocol data can have the chance to utiliz the network bandwidth simultaneously. In this paper, we investigate the friendliness of DCCP towards another transport protocol TCP over large delay link networks when carrying constant bit rate data. The result showed that DCCP is TCP friendly and it can coexist with TCP harmonically over large delay link networks.